MOLECULAR MARKER (PCR-RFLP) ASSISTED IDENTIFICATION OF MEAT SPECIES BY MITOCHONDRIAL CYTOCHROME C OXIDASE SUBUNIT I (COI) GENE - A. Khalid; M. Imran; A. Ali; S. Muzammil; M. Badar; S. Hayat; I. R. Malik (Journal of Animal and Plant Sciences, 2022)
To guard consumers from meat adulteration, there is a dire obligation to encompass a sensitive, simple, and precise way for the identification of meat animal species. Molecular techniques have hoisted the expectations of developing authentic and reliable methods for testing the origin of meat species. This study explains the utilization of Polymerase Chain Reaction and Restriction Fragment Length Polymorphism along with mitochondrial cytochrome c oxidase subunit I gene to identify six meat species i.e., buffalo (Bubalus bubalis), cow (Bos indicus), cat (Felis catus), goat (Capra hircus), donkey (Equus asinus) and sheep (Ovis aries). Universal primers were utilized to amplify a specific region (approx. 710 bp) encoding the mitochondrial COI gene in each species and after insilico analysis two restriction enzymes (TasI and TruI) were selected to digest all desired amplicons. Restriction analysis on 3% agarose gel uncovered unique species-specific restriction profiles. The level of COI variation by utilizing TasI and TruI was found to be adequate to produce effectively analyzable species-specific profiles that could recognize all species unambiguously. This study suggested that PCR-RFLP is a swift and reliable scheme in favor of recognition and discrimination of analyzed meat species by mitochondrial COI gene and can be employed in food control laboratories.
Keywords: PCR-RFLP; Mitochondrial COI gene; Molecular markers